The Later Privy Council and a Distinctive New Zealand Jurisprudence: Curb or Spur? - Baragwanath, David (Victoria University of Wellington Law Review, 2012)
The Privy Council was New Zealand's final court from 1840 until 2004. Its influence was largely benign, correcting errors of principle and, both in the early days and very recently, affording protection to Māori. But despite important exceptions, its failure to fully acknowledge New Zealand's independent identity, seen most importantly in its refusal during five of its final six decades to acknowledge the true legal effect of the Treaty of Waitangi, delayed the evolution of a distinctive New Zealand jurisprudence.